Madness in Fiction Literary Essays from Poe to Fowles - Axelrod-Sokolov, Mark (Springer International Publishing, 2018)
This book examines one work from each of five prominent authors dealing with madness. Including discussion of Fowles, Hamsun, Hesse, Kafka, and Poe, it delineates the specific type of madness the author associates with each text, and explores the reason for that - such as a historical moment, physical pressure (such as starvation), or the author's or his narrator's perspective. The project approaches the texts it explores from the perspective of a writer of fiction as well as a critic, and discusses them as unique manifestations of literary madness, treating them stylistically as unique experiments. It is of particular note for readers of fiction, of literary criticism and to those interested in psychology.